Collective Actions of Solidarity against Food Insecurity. The impact in terms of Capabilities. - Bernaschi, Daniela (Springer VS, 2020)
This book analyzes the issue of food insecurity in Europe. It highlights the role played by cities in promoting resilient, solidarity-based and food and nutritionally safe communities. The focus will be on three different local initiatives in Rome, Barcelona and Athens and on the relations between civil society and local public institutions in order to tackle with the food insecurity challenges. The aim of. The research is aimed at understanding the paradox of food insecurity in wealthy societies. The focus will be on three European countries: Italy, Spain and Greece. An in-depth analysis on collective actions of solidarity to tackle food insecurity, will assess whether the initiatives are capabilities-oriented or merely compensating for shortcomings. Moreover, the contributions to the definition of a new food policy “by” and “for” the cities will be highlighted.
Keywords: Stadtsoziologie; Ernährung; Nahrungsmittel; Lebensmittelversorgung; Unsicherheit; Armut; Solidarität; Bürgerengagement; Verantwortungsbewusstsein; Daseinsvorsorge; Sozialinfrastruktur; Lebenslage; Soziales Netzwerk; Ernährungsunsicherheit